2011
DOI: 10.1021/am200948p
|View full text |Cite
|
Sign up to set email alerts
|

New Silicon Architectures by Gold-Assisted Chemical Etching

Abstract: Silicon nanowires (SiNWs) were produced by nanosphere lithography and metal assisted chemical etching. The combination of these methods allows the morphology and organization control of Si NWs on a large area. From the investigation of major parameters affecting the etching such as doping type, doping concentration of the substrate, we demonstrate the formation of new Si architectures consisting of organized Si NW arrays formed on a micro/mesoporous silicon layer with different thickness. These investigations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 43 publications
(61 reference statements)
2
68
0
Order By: Relevance
“…The only difference may be the diffusion process of the ions whereby MacEtch will rely on solid-state diffusion instead. This new understanding will also explain discrepancies between the work from Mikhael et al 46,. who observed the presence of Au particles on the sidewalls of fabricated SiNWs, and that from Chiappini et al 47,.…”
Section: Resultsmentioning
confidence: 79%
“…The only difference may be the diffusion process of the ions whereby MacEtch will rely on solid-state diffusion instead. This new understanding will also explain discrepancies between the work from Mikhael et al 46,. who observed the presence of Au particles on the sidewalls of fabricated SiNWs, and that from Chiappini et al 47,.…”
Section: Resultsmentioning
confidence: 79%
“…In fact, n-doped Si was found to be etched faster than p-doped Si [17,23], and the etching rate decreases with increasing dopant concentration for both n- and p-doped Si [11,17,24]. Meanwhile, Li et al reported that the etching rate showed only small variation for a Au-coated p + , p − , and n + Si substrate and a Pt-coated Si was etched faster compared with a Au-coated Si [25].…”
Section: Resultsmentioning
confidence: 99%
“…The crystallographic orientation and the doping properties of the Si substrate, the type and the structure of a noble metal, the component and the concentration of the etching solution, temperature, illumination, and so on were reported to have a substantial effect on the etching rate [11,12,14-17]. In the present study, the thickness of the Au catalyst film, which is a new control dimension, was found to affect the etching rate of Si during the fabrication of SiNWs by a method that combines the anodic aluminum oxide (AAO) template and the metal-assisted chemical etching.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed fabrication procedure can be found elsewhere [8,9]. The ALD of Al 2 O 3 was carried out with a Cambridge Nanotech Savanah 200 system.…”
Section: Experimetal Detailsmentioning
confidence: 99%